Desain Speed Bump Penyimpan Energi Berbasis Sensor Piezzoelektrik - Zainal Abidin; Ulul Ilmi; M. Feri Bani Ashari (Universitas Darul Ulum, 2022)
Study aims to help carry out the use of the function of the speedbump or better known as the speed bump which is often found in Indonesia. The number of vehicles that cross the road with the speedbump installed makes the author want to develop the force generated from the speedbump whether it can produce electrical energy through the piezoelectric effect, from this problem the author took the initiative to create a tool that can generate alternative electrical energy. This tool is made of several main circuits, namely piezoelectric sensors to generate electrical energy, charging control as a means of charging the battery. the battery as a reservoir of power generated from the piezoelectric sensor, LED lights as the output of the power generated by the piezoelectric sensor for street lighting. All assembled into a single unit into a miniature device. Based on the results of experiments that have been carried out by comparing the effectiveness and efficiency of the tool with the results of other similar tools, the difference between the two tests of the tool is not much different and is still at the same limit.